The Concept of Criminal Responsibility in Islamic Criminal Law - Hidayani, Sri; Mina, Revi Fauzi Putra (Universitas Islam Negeri Sumatera Utara, 2022)
Criminal law in Islam is an integral part of the Islamic legal system that regulates the behavior of individuals in society. The concept of criminal liability is an important aspect of this legal system, which includes various rules and principles governing how individuals are held accountable for criminal acts committed. This research aims to explain the concept of criminal liability in Islamic criminal law, focusing on the main principles related to law enforcement and punishment. The research method used is a normative juridical approach, which involves the study of Islamic legal doctrine, analysis of Islamic legal texts, and comparison with other criminal law systems. The results show that in Islamic criminal law, criminal responsibility does not only include aspects of punishment for criminal acts, but also considers aspects of guidance and rehabilitation. Principles such as ta'zir, hudud, and qisas become the foundation for criminal liability in Islamic criminal law, with the aim of maintaining justice, order, and security in society. The conclusion of this research is that the concept of criminal liability in Islamic criminal law has great relevance in the context of law enforcement and social justice. However, the protection of human rights and the principles of justice must also be upheld in the application of Islamic criminal law. Therefore, further research and interfaith dialog are important to deepen the understanding of the concept of criminal responsibility in Islamic criminal law and its application in the contemporary context.